Developing English Beginner Material for Adult Level Integrated into Web Mobile - Agus Triyogo; Maria Ramasari; Hamdan Hamdan; Wicaksono Febriantoro (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
English is an international language which uses as language communication by people in the world with different language backgrounds, by English people have easy-to-do relationships with other people oversea. Looking at the larger of English users in the world, Indonesian must try to follow by learning English to make interaction with other people in the global area. English be one of the scrim lessons in the school because it contrasts with   Indonesia Language in vocabulary, pronunciation and vocabulary. Such as in the physic study program at STKIP PGRI Lubuklinggau as 1. Difficult to master English vocabulary, 2. Confuse how to utter words, 3. Do not understand grammatical in writing and speaking. In another hand, they also need some books that able to cover all skills easy to be master such as 1. They need a guidebook which has a lot of vocabulary with meaning, 2. There are guides on how to utter vocabulary, 3. A lot of samples and practice in fours English skills. 4. Book must be practised and interactive. Based on the problem above, researchers tried to develop beginner English material based on web mobile for adults. The method of research was Research and Development with the model of ADDIE. The purpose of this research is to Produce Beginner English material based on Web Mobile. The result shows that based on the judgment from the experts got a score of 3.48, which means the e-model validation was valid. The results of the assessment of student responses to the e-module in the completed questionnaire obtained an average overall assessment score of 3,34 with a very good product category. The outcomes from the research are articles published in national journal indexes by Sinta and an English module based on Web Mobile.